A Fluorescent Turn‐on Probe Based on Zn‐doped AgIn5S8 Quantum Dots for Imaging of Hydrogen Sulfide in Living Cells. Issue 43 (18th November 2020) - Dong, Yanyu; Sun, Wenping; Chang, Shiqi; Li, Tong; Huang, Xiaohua; Xing, Shanghua; Bai, Tianyu; Ma, Huipeng
Abstract: H2 S has been identified as endogenously generated gasotransmitter in mammalian which acts essential role in various physiological and pathological processes. In this work, we reported the use of hydrophilic, low‐toxic and photostable Zn‐doped AgIn5 S8 quantum dots (ZAIS QDs) in H2 S detection. Copper ions, acting as recognition moieties, are conjugated on the surface of ZAIS QD to construct the fluorescent probe. The weak fluorescence signal of the probe owing to the quenching effect of paramagnetic Cu 2+ center on ZAIS QDs can exhibit significant fluorescence turn‐on property upon the addition of H2 S. Simultaneously, the probe possesses high sensitivity at physiological pH, excellent membrane permeability and dose‐dependent fluorescence imaging of exogenous H2 S in living cells. Abstract : We reported a fluorescent turn‐on probe consisting of Zn‐doped AgIn5 S8 QDs as fluorophore moieties and Cu 2+ as recognition moieties. The ZAIS‐Cu probe exhibited favorable H2 S response properties, such as high sensitivity with detection limit of 0.9 μM, good selectivity over most representative interferents, well function at physiological pH, and dose‐dependent fluorescence imaging of exogenous H2 S in living cells, validating its the potential ability to be used as a practivally useful tool for further studying biological roles of H2 S.